Pinocytic rates of macrophages from mice immunized against Toxoplasma gondii and macrophages stimulated to inhibit toxoplasma in vitro. - Jones, T C (1976)
The rate of pinocytosis by macrophages when measured by uptake of horseradish peroxidase was significantly reduced during toxoplasma infection of the cells in vitro when the macrophages were from toxoplasma-immune mice and when control cells were stimulated in vitro to inhibit toxoplasma multiplication. There was, however, no direct correlation between reduced pinocytosis in this model and inhibition or enhancement of toxoplasma multiplication. We conclude that a reduced pinocytic rate is a feature of the unstimulated toxoplasma-immune macrophage, but this change in rate alone does not correlate with the cell's ability to inhibit toxoplasma. In addition, we observed that enhanced pinocytosis as seen in the elicited macrophage was not a requirement for inhibition of toxoplasma multiplication.